Effects of Fit Clearance Between the Outer Ring and the Housing on Vibration Characters of the Gear-shaft-bearing System - Xu Lijin; Chen Qing; Dai Peng; Wang Fengtao (Jixie chuandong)
Gear-shaft-bearing systems are commonly used in transmission mechanisms. When there are fit clearances between the bearing outer ring and the bearing housing, complex vibration responses will be generated, which makes the recognition of operating status more difficult. Thus, a 36 DOFs model of the gear-shaft-bearing system with bearing fit clearances is established. In this model, the gear pair system and the bearing system are combined, the collision force and friction force caused by the fit clearance are considered, which are calculated by the nonlinear contact in Hertz theory and Coulomb friction model. The results show that when there are fit clearances on the bearing, the amplitude modulation of the bearing outer raceway to the system time-domain response is exacerbated. The larger the fit clearance is, the more serious the amplitude modulation will be. Due to the increase in the number of attenuations, the multiple harmonic components of gear pairs and bearings are generated on the spectrum. As the bearing fit clearance is increased, the higher multiple harmonic components will be generated. Finally, the established model and the analysis of the results are verified by experiments.